Arcadia [large type] - Groff, Lauren (Thorndike Press large print basic series., 2012)
In the fields of western New York State in the 1970s, a few dozen idealists set out to live off the land, founding a commune on the grounds of a decaying mansion called Arcadia House. They include Abe, a master carpenter; Hannah, a baker and historian; and Abe and Hannah's only child, Bit, born soon after the commune. Through Bit, Arcadia follows this romantic, rollicking, and tragic utopian dream from its hopeful start through its heyday and beyond. (Bestseller)